The Playa Hermosa formation, Playa Verde basin, Uruguay - Pazos, Pablo Jose; Rapalini, Augusto Ernesto; Bettucci Sanchez, Leda; Tofalo, Ofelia Rita de Las Mercedes (Geological Society, London, Memoirs)
The Playa Hermosa Formation (Fm.) (Playa Verde Basin) is a volcano-sedimentary unit that crops out in the extreme south of the Dom Feliciano Belt in Uruguay. This formation has traditionally been interpreted as non-glacial in origin, but recently it has been suggested that the lower part at least may be glacially influenced. The stratigraphic position of the Playa Hermosa Fm. and its correlation with other Neoproterozoic units of Uruguay, Argentina and southern Brazil remains in dispute. An age of c. 580 Ma is indicated by a hornblende 39Ar/40Ar age on magmatism regarded as coeval with syn-sedimentary volcanism. Preliminary palaeomagnetic data suggest a primary remanence and a mean geomagnetic pole consistent with the proposed apparent polar wander path for the Río de La Plata craton. In combination, these data suggest mid-Ediacaran glacial sedimentation in low to intermediate latitudes on the Río de la Plata craton. However, this conclusion needs to be reinforced by more thorough studies of the age and origin of the Playa Hermosa Fm. Fil: Pazos, Pablo Jose. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Geológicas; Argentina Fil: Rapalini, Augusto Ernesto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Geológicas; Argentina Fil: Bettucci Sanchez, Leda. Facultad de ...